Utopia in performance: re-imagining a coloured identity narrative - Wentworth, Raezeen (Department of Drama, 2019)
In this study I explore how coloured identity has been historically produced as a monolithic racial category, focussing on how performance offers critically generative ways of addressing and contesting the politics and meanings of colouredness in post-apartheid South Africa. This study explores the politics of naming in so far as its impact both from an intrinsic and extrinsic perspective in relation to a personal identity narrative. It is the interest of this study is to disrupt normative ideological and cultural constraints and investigate the performance of coloured identity through the use of individual and collective memory construed from the established theatrical canon. The desired outcome is to unearth a series of practical reference points towards the performance of a progressive coloured identity narrative within the current socio-cultural and political landscape. The theoretical body though which this practice is located is framed though a critical definition of 'Utopia’, in an attempt to mobilise how the narrative of coloured identity could be explored in the realm of theatrical performance. I propose that it is within a utopian performative space; one that is reflexive of the past and that is non-coercive; that a re-imagining of a coloured identity narrative is made accessible.